Cover Feature: Oxygen‐Doped PAH Electrochromes: Difurano, Dipyrano, and Furano‐Pyrano Containing Naphthalene‐Cored Molecules (Eur. J. Org. Chem. 2/2022). Issue 2 (14th January 2022) - Fletcher‐Charles, Jack; Ferreira, Rúben R.; Abraham, Michael; Romito, Deborah; Oppel, Markus; González, Leticia; Bonifazi, Davide
Abstract : The Cover Feature shows the color changes achieved, upon oxidation, by newly synthesized electrochromic oxygen‐doped small molecules. The crucial moieties are furano and pyrano. Incorporation of these groups into other organic molecules can be used to greatly expand the library of electrochromic small molecules, giving very good control over color transition observed. Such controlled color changes could take electrochromism from the niche applications it currently occupies, to the wider world. Cover design by Adriana Lopez‐Biagi. More information can be found in the Full Paper by D. Bonifazi et al .